Camera‐trapping provides insights into adult sex ratio variability in felids. (7th March 2018) - Anile, Stefano; Devillard, Sebastien
Abstract: Adult sex ratio (ASR) plays a pivotal role in many ecological processes, such as population dynamics in time and space, extinction risk and reproductive success, but few patterns in the variability in ASR have been found across species. Due to the socio‐spatial structure and polygynous mating system found in felids, ASR is expected to be female‐biased in felids in a finite area; however, ASR is also commonly found to be either balanced or male‐biased in this taxonomic group. Therefore, investigating ecological correlates of the pattern of ASR variability in felids is of prime importance both for a better understanding of evolutionary ecology and for a more evidence‐based conservation of these threatened taxa. The aim of this review was to investigate whether the expected female‐biased ASR occurs in felids, and whether ASR is influenced by the size of the study area, the species' body mass and the population density, taking into account the species‐specific home‐range requirements. We reviewed the camera‐trapping literature on felids to build a large global multi‐species data set on ASR variation. We used general linear mixed models to investigate ecological correlates of ASR. In small study areas, the ASR was balanced for all species, but in large areas the ASR was female‐biased for large and medium cats and male‐biased for small cats; sampling designs that are unsuitable for small cats (due to 'gaps' within the trapping grid) might explain this latter finding. Moreover, in large study areas, an increase in cat density was associated with more females, whereas in small areas the reverse was true. Our study provides a scientifically sound background for management and conservation actions of these flagship‐threatened taxa of carnivores, by indicating the importance of the study area on ASR in felids. Large areas can promote the recovery of large and medium cats, as more females can be hosted.